(untitled) (Research, Society and Development, 2026)
Endodontic treatment aims to achieve effective cleaning and sealing of the root canal system in order to eliminate microrganisms and prevent reinfection. Among the irrigants used in endodontics, sodium hypochlorite (NaOCl) stands out due to its antimicrobial activity and tissue-dissolving capacity. However, its effectiveness is directly related to concentration and contact time, which may also increase the risk of cytotoxicity and adverse effects on dentin. Therefore, this study aimed to critically evaluate the scientific literature regarding the use of NaOCl in endodontic irrigation, with emphasis on ideal concentration, exposure time, antimicrobial effectiveness, and possible adverse effects. This is a bibliographic review conducted through a search in the PubMed database using the descriptor “sodium hypochlorite irrigation,” applying filters for publications from the last five years. Of the 1.011 records initially identified, 12 articles met the inclusion criteria and were selected for analysis. Subsequently, 3 additional relevant studies were included, resulting in a total of 15 analyzed articles, most of which were published in high-impact journals. Based on the analysis performed, it was noted that NaOCl remains the irrigant of choice in endodontics, due to its excellent antimicrobial action and good tissue dissolution potential. It has been observed that higher concentrations and longer contact times increase the effectiveness of NaOCl, but also increase its potential to cause undesirable effects on the dentin structure.